Moment Oporowy Cienkiej Tarczy Wirującej w Osłonie (Laminarne Przepływy Wtórne) - Gryboś, R. (Engineering Transactions, 1973)
The considerations concern a thin, smooth disk rotating in a cover which is filled by a viscous, incompressible fluid. Laminar, three-dimensional flow in the boundary layers is assumed, and also the existence of a "fluid core" rotating between these layers. On the basis of the Navier-Stokes equations, the continuity condition and the angular momentum principle, the formula is derived for the frictorial torque of the disk and of the plane walls of the cover, the angular velocity of the core being also determined. Equation (5.5) for the frictorial torque coefficient yields the results which comply with the measurements within the interval 104< Re